Collaboration on the Complete Systematic Land Registration Program (PTSL) between the Central and Regional Governments as a Political Tool - Osman Affan; Anwar harun Damanik; Mu’ammar Mu’ammar; Luhut Fedrik Rio; Dedeh Maryani (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
The Complete Systematic Land Registration Program (PTSL) is a strategic government initiative to provide legal certainty over land rights and ensure orderly land administration. This study aims to analyze the mechanisms of collaboration between the central and regional governments in implementing PTSL and examine the program's function as a political instrument. Using a qualitative approach, this study finds that the success of PTSL is highly dependent on policy synergy, budget support, and human resource capacity at both levels of government. Politically, the success of PTSL strengthens government legitimacy and increases electoral support, but also carries the risk of bureaucratic politicization and distributional inequality if not closely monitored.